Ability of the GENSPEED® MRSA test kit to detect the novel mecA homologue mecC in Staphylococcus aureus. Issue 6 (23rd April 2015) - Petersen, Andreas; Medina, Alexandra; Larsen, Anders Rhod
<x xml:space="preserve">Abstract</x> The aim of this study was to evaluate the GENSPEED® MRSA Test Kit that in addition to the traditional MRSA gene mecA, also incorporates a probe for detection of the newly described mecA homologue mecC. So far only one commercial system is able to detect this new gene. The specific objective was to evaluate the ability of the kit to detect and separate Stapyhylococcus aureus containing either mecA, mecC or no methicillin‐resistance determinant. Ninety‐five MRSA isolates from humans were included in the test and additional mecC‐positive isolates from animals and methicillin‐sensitive S. aureus were tested. The kit demonstrated 100% sensitivity and 100% specificity compared to a standard PCR method. The kit provides the ability to perform rapid and reliable detection of both mecA‐MRSA and mecC‐MRSA.